Apelin-13 protects the heart against ischemia-reperfusion injury through the RISK-GSK-3β-mPTP pathway - Yang, Shuansuo (Arch Med Sci, 2015)
INTRODUCTION: Apelin plays an important role in the protection against myocardial ischemia-reperfusion (I/R) injury, while the mechanism still remains unclear. In the current study, we aimed to evaluate the protective effect of apelin-13, and the main mechanism. MATERIAL AND METHODS: The in vivo I/R injury model (Sprague-Dawley rat) was established, then infarct size, expression levels of phospho-protein kinase B (p-Akt), phospho-extracellular signal-regulated kinase (p-ERK) and phospho-glycogen synthase kinase-3β (p-GSK-3β) were measured. The fluorescence intensity of tetramethylrhodamine ethyl ester perchlorate (TMRE) of the isolated myocardial cells was determined to evaluate the opening of the mitochondrial permeability transition pore (mPTP) caused by oxidant stress and hypoxia/reoxygenation. RESULTS: For the established I/R injury model, apelin-13 and SB216763 (GSK-3β inhibitor) significantly reduced the infarct size (p < 0.05), which could be abolished by LY294002 (PI3K inhibitor), PD98059 (MEK inhibitor) and atractyloside (mPTP accelerator). The enhanced expression levels of p-Akt, p-ERK and p-GSK-3β caused by apelin-13 (p < 0.05) could be counteracted by LY294002 and PD98059. The reduced fluorescence intensity of TMRE in the H(2)O(2)/apelin-13 and H(2)O(2)/SB216763 treated groups was significantly lower (p < 0.05), indicating that apelin-13 and SB216763 could reduce the decline in mitochondrial membrane potential caused by oxidant stress, and the fluorescence intensity in the hypoxia/reoxygenation + apelin-13 group was significantly lower (p < 0.05), which suggested that apelin-13 could inhibit the mitochondrial membrane potential changes induced by hypoxia/reoxygenation. CONCLUSIONS: The protective mechanism of apelin-13 might be that inactivation of GSK-3β could inhibit the opening of mPTP by activating PI3K/Akt and ERK1/2 involved in the reperfusion injury salvage kinase (RISK) pathway.